The Arabidopsis Circadian Clock and Metabolic Energy: A Question of Time - Cervela-Cardona, Luis; Alary, Benjamin; Mas, Paloma (Frontiers in Plant Science, 2021)
A fundamental principle shared by all organisms is the metabolic conversion of nutrients into energy for cellular processes and structural building blocks. A highly precise spatiotemporal programming is required to couple metabolic capacity with energy allocation. Cellular metabolism is also able to adapt to the external time, and the mechanisms governing such an adaptation rely on the circadian clock. Virtually all photosensitive organisms have evolved a self-sustained timekeeping mechanism or circadian clock that anticipates and responds to the 24-h environmental changes that occur during the day and night cycle. This endogenous timing mechanism works in resonance with the environment to control growth, development, responses to stress and also metabolism. Here, we briefly describe the prevalent role for the circadian clock controlling the timing of mitochondrial activity and cellular energy in Arabidopsis thaliana. Evidence that metabolic signals can in turn feedback to the clock place the spotlight onto the molecular mechanisms and components linking the circadian function with metabolic homeostasis and energy.